Cadmium interference with iron sensing reveals transcriptional programs sensitive and insensitive to reactive oxygen species. (9th September 2021) - McInturf, Samuel A; Khan, Mather A; Gokul, Arun; Castro-Guerrero, Norma A; Höhner, Ricarda; Li, Jiamei; Marjault, Henri-Baptiste; Fichman, Yosef; Kunz, Hans-Henning; Goggin, Fiona L; Keyster, Marshall; Nechushtai, Rachel; et al.
Abstract: Iron (Fe) is an essential micronutrient whose uptake is tightly regulated to prevent either deficiency or toxicity. Cadmium (Cd) is a non-essential element that induces both Fe deficiency and toxicity; however, the mechanisms behind these Fe/Cd-induced responses are still elusive. Here we explored Cd- and Fe-associated responses in wild-type Arabidopsis and in a mutant that overaccumulates Fe ( opt3-2 ). Gene expression profiling revealed a large overlap between transcripts induced by Fe deficiency and Cd exposure. Interestingly, the use of opt3-2 allowed us to identify additional gene clusters originally induced by Cd in the wild type but repressed in the opt3-2 background. Based on the high levels of H2 O2 found in opt3-2, we propose a model where reactive oxygen species prevent the induction of genes that are induced in the wild type by either Fe deficiency or Cd. Interestingly, a defined cluster of Fe-responsive genes was found to be insensitive to this negative feedback, suggesting that their induction by Cd is more likely to be the result of an impaired Fe sensing. Overall, our data suggest that Fe deficiency responses are governed by multiple inputs and that a hierarchical regulation of Fe homeostasis prevents the induction of specific networks when Fe and H2 O2 levels are elevated. Abstract : Cadmium induces an iron deficiency response often explained by root uptake competition. Here we show that Cd also impairs Fe sensing in leaves, even when Fe is in sufficient quantities.